Analisis Sikap Spiritual dalam Buku Teks Siswa Pai dan Budi Pekerti Untuk SD/MI Kelas V Terbitan Kemdikbud Berdasarkan Perkembangan Anak - Riski Noura Arista (Pusat Studi Pendidikan Kreatifitas Anak Wadas Kelir Purwokerto, 2019)
Textbooks as compulsory reference books used in basic education units have beensystematically compiled based on a particular curriculum and through selection tailoredto the learning objectives, learning orientation and referring to the needs anddevelopment of students. Because of the need for different stages of development ofstudents in each level of education, the accuracy in the selection of the use of textbooksthat are appropriate to the development of students is very important. This paper aimsto find out the spiritual attitudes found in student textbooks. The student textbooksanalyzed were textbooks of Islamic Education and Character Education students forgrade V SD / MI 2017 revised edition of the 2013 Curriculum published by the Ministry ofEducation and Culture. The method used in this research is descriptive analysis method.The result of this finding is that the aspect of spiritual attitudes in this student textbookis very complex. Because in this textbook there are seven spiritual attitudes that mustbe mastered by children. Namely accepting religious teachings; where children areconditioned to believe in Allah and believe that the apostle as a messenger of Allah, carryout religious teachings; children are directed to get used to reading the Qur'an and showcommendable behavior, and respect religious teachings; children are conditioned torespect others who have different beliefs and opinions. From these attitudes, in termsof aspects of child development, it is in accordance with the child's development whichis in accordance with the child's ability domain.